The art of scenic design : a practical guide to the creative process - Morgan, Robert Mark (Introductions to theatre, 2022)
"How do you navigate a career as an entertainment designer and work collaboratively to achieve creative goals? The Art of Scenic Design provides an in-depth look at the scenic design process for young designers as well as creative entrepreneurs seeking to nurture a collaborative environment that leads to rediscovery and innovation in their work. Based on 30 years of experience in stage and exhibit design, art direction for film, and theme park and industrial design, Morgan guides readers through the theatrical design process from early phases through to its execution and manifestation with a team of artisans"--